The Use of Clay Media to Improve Color Knowledge and Science Knowledge in The Exploration Process of Early Childhood - Ramadhani, Dewi Maulidia; Nurhalimah, Evi (Manunggal Halim Jaya, 2025)
Clay media is a clay-like media that is easy to shape and has various colors. This media is safe and easy to use by early childhood to explore various types of knowledge and skills according to the child's development period. This study aims to analyze the use of clay media to improve color knowledge and science knowledge in early childhood. The research method is qualitative descriptive research with literature study analysis techniques. The findings show that the use of clay media can improve color knowledge in early childhood. From clay media play activities, early childhood is able to point to the colors mentioned, mention various types of colors, and construct new colors so that it shows increased color knowledge. Clay media can also improve science knowledge in early childhood with activities to form clay media into plant structures or types of animals. Teachers can provide simple explanations related to living things so that children can understand the material in a fun way. This activity can stimulate children's understanding of living things as part of biology and science learning. Basically, early childhood needs sensorimotor stimulation and direct experience to be able to develop cognitive knowledge and skills. Thus, it is hoped that teachers can utilize the learning method of playing with clay media to support the knowledge and skills of early childhood that are appropriate to their development period.